Selective Binding of DNA Origami on Biomimetic Lipid Patches. Issue 43 (21st September 2015) - Hirtz, Michael; Brglez, Josipa; Fuchs, Harald; Niemeyer, Christof M.
Abstract : Arrays of biomimetic lipid patches for studying the binding of DNA origami structures can be tailored in size, shape, and composition with the aid of lipid–dip pen nanolithography. This approach allows for analysis of the effects of lipid composition with high throughput which could be applied for the targeted presentation of functional DNA origami structures on surfaces.